Role of G-CSF in monophosphoryl lipid A-mediated augmentation of neutrophil functions after burn injury - Bohannon, Julia K. (J Leukoc Biol, 2016)
Infection is the leading cause of death in severely burned patients that survive the acute phase of injury. Neutrophils are the first line of defense against infections, but hospitalized burn patients frequently cannot mount an appropriate innate response to infection. Thus, immune therapeutic approaches aimed at improving neutrophil functions after burn injury may be beneficial. Prophylactic treatment with the TLR4 agonist monophosphoryl lipid A is known to augment resistance to infection by enhancing neutrophil recruitment and facilitating bacterial clearance. This study aimed to define mechanisms by which monophosphoryl lipid A treatment improves bacterial clearance and survival in a model of burn-wound sepsis. Burn-injured mice were treated with monophosphoryl lipid A or vehicle, and neutrophil mobilization was evaluated in the presence or absence of Pseudomonas aeruginosa infection. Monophosphoryl lipid A treatment induced significant mobilization of neutrophils from the bone marrow into the blood and sites of infection. Neutrophil mobilization was associated with decreased bone marrow neutrophil CXCR4 expression and increased plasma G-CSF concentrations. Neutralization of G-CSF before monophosphoryl lipid A administration blocked monophosphoryl lipid A-induced expansion of bone marrow myeloid progenitors and mobilization of neutrophils into the blood and their recruitment to the site of infection. G-CSF neutralization ablated the enhanced bacterial clearance and survival benefit endowed by monophosphoryl lipid A in burn-wound-infected mice. Our findings provide convincing evidence that monophosphoryl lipid A-induced G-CSF facilitates early expansion, mobilization, and recruitment of neutrophils to the site of infection after burn injury, allowing for a robust immune response to infection.